Efek Ekstrak Petroleum Eter Daun Ara (Ficus Racemosa Linn.) pada Indeks Fagositosis Mencit (Mus musculus) - Candra Dwipayana Hamdin; Andriliana Trihastuty; Siti Rahmatul Aini (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Terpenoid compound from ara’s leaf is known to have immunosuppressant activity by inhibit blood cells proliferation. Immunosuppressant is a group of drugs that can suppress excessive immune responses. The aim of this research was investigated the immunosuppressant effect of petroleum ether from ara’s leaf (Ficus racemosa Linn.) on mice (Mus musculus). The immunosuppressant activity was conducted by carbon clearance method to investigate the ability of phagocytosis with carbon as an antigen that is injected intravenously, followed by determining organ index. All data was analyzed by SPSS. The result showed that at dose of 560 mg/kgbw and 1120 mg/kgbw, extract found to have immunostimulant activity with phagocytic index values respectively ​​of 1.5 and 1.1, while the dose of 1680 mg/kgbw was immunosuppressant with phagocytic index 0.7. The lymphoid organ index showed a significantly difference between petroleum ether from ara leaf extract by dose 1680 mg/kgbw with negative control (p<0.05). Based on the results of the non-specific immune response, it can be concluded that the petroleum ether ara’s leaf extract by dose 1680 mg/kgbw has immunosuppressant activity.